The Concept of Local Economic Organization As An Instrument to Support Local Entrepreneurship - Agnieszka WÓJCIK-CZERNIAWSKA; Hieronim Jedrzejewski (Communications of International Proceedings, 2022)
Supporting local entrepreneurship by business environment institutions is essential for activating relations of local stakeholders. In the economic and social space, there are many business environment institutions supporting the economy and acting on many levels of stakeholder connections. Local economic organizations are a proposal to build and activate relations at the local level within the commune. An important role in this activation is played by local governments which, apart from carrying out their activities within the scope of their competences, play the role of an intermediary between all local stakeholders, in particular SMEs. Research on the impact of these relationships on local entrepreneurship was carried out in 2020 as part of the first stage of the Regiogmina project. The conducted research was aimed at identifying the existing mechanisms of enterprise support by local governments in Poland and in 14 European countries, as well as in South Korea and the USA, and covered the area of ​​cooperation mechanisms between local governments and entrepreneurs. As a result of the research, the concept of a local economic organization (LOG) was proposed as a formal institution supporting local entrepreneurship at the commune level, the initiator and supporting entity of which will be the local government, but it will be appointed and supervised by local entrepreneurs. The second stage of the implementation project allowed to present the developed concept to local governments and local entrepreneurs in selected municipalities and to initiate preparations for the establishment of such organizations. The purpose of this study is to present the concept of the LOG and to present preliminary conclusions from the implementation part of the project as a pilot. Support for local entrepreneurship by the institutions of the business environment is essential to activate the relationships of local actors. In the economic and social space, there are many institutions in the business environment that support the economy and act at many levels of relationships with stakeholders. Local economic organizations are a proposal to build and activate relationships at the local level within the commune. An important role in this activation is played by local governments which, in addition to carrying out their activities within the scope of their powers, play an intermediary role between all local actors, in particular SMEs. Research on the impact of these relationships on local entrepreneurship was carried out in 2020 as part of the first stage of the Regiogmina project [1]. The research carried out aimed to identify the existing mechanisms of business support by local governments in Poland and in 14 European countries, as well as in South Korea and the USA, and covered the area of cooperation mechanisms between local governments and businesses. As a result of the research, the concept of a local economic organization (LOG) was proposed as a formal institution to support local entrepreneurship at the community level, whose initiator and support entity will be the local government, but [1] The project "Location at the local government level of support instruments for SMEs operating on the basis of the multilevel regional management model (REGIOGMINA)" is implemented by the Kujawsko-Pomorskie Voivodeship consortium as project leader and the Warsaw School . of Economics and the Nicolaus Copernicus University in Toruń and financed by the National Center for Research and Development under the Strategic Program: "Social and economic development of Poland in the conditions of globalized markets" GOPOSTRATEG.